Success is an Open Book: Online Diagnostic Tools and Learning Outcomes in Introduction to American Government Courses. Issue 1 (2nd January 2016) - Reed, Ryan; Smith, Daniel E.
ABSTRACT: This project examines the utility of a particular course enhancement, Cengage's Aplia, and more generally interactive tools designed to facilitate reading in the introductory American government course. Using two control and two treatment sections of the course (one section each for two instructors) during the Fall 2013 term, we measured student performance, engagement, and interest in the subject matter. While there was no statistically significant benefit regarding interest level, use of Aplia resulted in improved performance and engagement in the course. We conclude that, subject to further study, the Aplia diagnostic quizzes offer tangible benefits in teaching the introductory American government course and offer further insights regarding these benefits.